‘Symbols of Bird, Blood, and Sleep in William Shakespeare’s ’Macbeth’’ - S, Arunakumari; Puttaiah, Venkatesh (International Journal of Psychosocial Rehabilitation, 2024)
This paper attempts to explain the ’Symbols of Bird, Blood, and Sleep’ in Shakespeare’s Macbeth. The brief arrival of a trio of witches’ (sorceress) precognition leads Macbeth with his psychological consequences of irrepressible ambition to vanquish the desired realm by slaughter king Duncan. Shakespeare projected the deep-seated opinions of human beings as well as their values according to the situations, with the comparison of the different symbols. For example, with the restless ecstasy, sleep symbolizes innocence and purity and blood symbolizes murder and guilt, and the bird epitomizes both the superstitious aspect of negativity and evil power. In Shakespeare’s Macbeth, symbols play a significant role, as these symbols have been intertwined across the various characters and have been used in several ways to connect the general theme of murder to the action in the play of Macbeth and Lady Macbeth.